A study on serum calcium and magnesium levels in seizures disorders in pediatric age (Panacea Journal of Medical Sciences, 2022)
Introduction: Seizures are the most common neurologic disorder of childhood. A study was undertaken to find the correlation between serum Calcium and Magnesium levels and seizure disorders in pediatric age.Materials and Methods: It was a prospective case control time bound study, conducted in the department of paediatrics, Gandhi Medical College, Secunderabad. Study protocol was approved by the institutional ethics committee. Informed written consent was taken from the parents of the participants. Children of both gender, aged I month – 14 years with seizures were included, included in the test and non seizures in control category. After through clinical examination venous blood samples were collected for the estimation of serum electrolyte levels, 24 hours after onset of seizures on admission. T test was used to find the statistical significance and p > 0.05 was considered statistically significance.Results: The mean age was 8.6 and 7.8 years respectively in test and control groups. Seizures were diagnosed to be due togliosis, mesial temporal sclerosis, infarcts, hippocampal sclerosis, leighs disease.Statistically there was significant difference between the serum electrolyte levels.Conclusion: There was decrease in serum Ca and Mg levels with seizures. However, there was no correlation between serum electrolytes and severity of seizures.